Authentic Montessori: The Dottoressa’s View at the End of Her Life Part II: The Teacher and the Child - Lillard, Angeline S; McHugh, Virginia (Journal of Montessori Research, 2019)
Part II of this two-part article continues the discussion of what Maria Montessori viewed to be the important components of her educational system. Because she developed the system over her lifetime, we prioritized later accounts when contradictory accounts were found. Whereas Part I focused on the environment, Part II examines the second and third components of the Montessori trinity: the teacher and the child. This article includes descriptions of Montessori teacher preparation, children’s developmental stages, and the human tendencies on which Montessori education capitalizes. It ends with child outcomes as described by Dr. Montessori and as shown in recent research, and provides an appendix summarizing features of authentic Montessori described in Part I and Part II.